The Mountain Meadows Massacre of 1857: A Civilizational Encounter with Lessons for us All - Andregg, Michael M. (International Society for the Comparative Study of Civilizations, 2010)
Between September 7 and 11 of 1857 an emigrant wagon train was attacked while traveling through southern Utah toward California. In the end, about 120 were killed, sparing only 17 or perhaps 18 children considered too young to tell the tale. In the annals of war and slaughter this could be considered a tiny event. But for the history of the Great Basin of North America, it was quite exceptional. More white emigrants died on the Mountain Meadows than during any other violent event in the history of the American west. For civilizationalists this is important as a case study of civilizational encounter, because while complex, it has been studied in rare detail. Mormons in the area had arrived just ten years earlier with the expressed purpose of creating a new and morally better civilization than the one they had been violently expelled from. The Indians in the area were coping with a flood of white-skinned immigrants of many kinds who were killing off game and grazing on scarce grasses in a land more desert than not. And the emigrants who died were just passing through, on their way to dreams of riches further west. This confluence of forces and movements of people from many places combined with specific personalities of leaders and the history of a newly emerging religion with civilizational dreams to create a tragedy even the Greeks could scarcely contemplate. The slaughter was so complete and duplicitous that word of it spread across the continent rapidly. It had dramatic impacts on relations between Mormons and other Americans, some of which echo to this day in states like Arkansas. Therefore this paper will examine mainly those aspects, civilizational encounter and consequences.
This paper describes a little known but highly influential massacre of a Christian (or "Gentile") wagon train heading for California in 1857 which had to pass through Mormon territory known as Utah today. At least 120 people were slaughtered sparing only 17 (or perhaps 18) children thought too young to remember the details, partly because killing anyone under the age of 8 is strictly forbidden by Mormon theology. The slaughter took five days and was accomplished with such deception and duplicity that a movie was made of it called "September Dawn." Knowledge of this event was tightly suppressed by the LDS church for many years, and a cover story was quickly created that Indians had done the evil deeds. But the Bishop of the nearest Mormon "stake" had a conscience, drove the children spared in a wagon for distribution to Mormon families in the area, and ultimately testified to a court in Nevada about what really happened. His name was Philip Klingensmith. Klingensmith eventually fled to Mexico pursued by Mormon "Danites" (a kind of enforcers of doctrine in those early days of the church) where he was probably murdered, although that detail cannot be confirmed by this author.
Keywords: causes of wars; Mountain Meadows Massacre; History, Mormons